THE “CAUCASIAN TRIP” OF ARCHAEOLOGIST K.N. LYUBARSKY IN 1915 (BASED ON ARCHIVAL MATERIALS) - Kokorina, Ulia Georgievna; Vagabov, Mahac Mustafaevic (History, Archeology and Ethnography of the Caucasus, 2026)
This article serves as a source study, introducing a previously unknown historical document into scholarly circulation: the travel diary of archaeologists S.O. Dolgov and K.N. Lyubarsky during their 1915 expedition to the Caucasus. The diary is currently held in the K.N. Lyubarsky archive within the Department of Written Sources at the State Historical Museum. The relevance of this study lies in providing new insights into the history of Caucasian archaeology and shedding light on the personality of a lesser-known researcher dedicated to the preservation of regional antiquities. The novelty of the work is found in the presentation of these previously unpublished materials. The historiography of K.N. Lyubarsky’s career is minimal; a “romantic laborer” of science who perished during the Russian Civil War, his name remains largely unknown. The primary objective of this paper is to introduce the Russian scientific community to the life and work of this obscure researcher. Through an analysis of the source material, the article details investigations of Western Caucasian dolmens, mountain fortresses, and burial mounds containing stone cists. Significant attention is given to the excavation of fortress ruins on the Khosta River. The diary portrays Lyubarsky as a meticulous field researcher with a profound passion for science and a keen sensitivity to the Caucasian landscape. Although working within the methodological constraints of his era, Lyubarsky recognized their limitations, employing advanced recording techniques and prioritizing the conservation of monuments. This source documents the experience of studying antiquities during wartime – a testament to the efforts of Russian archaeologists to preserve cultural heritage that remains relevant today.